HUBUNGAN ANTARA PENGETAHUAN DENGAN SIKAP IBU USIA 40 â 45 TAHUN TERHADAP MENOPAUSE DI RW 04 SUKA MULYA WILAYAH KERJA PUSKESMAS SAIL PEKANBARU TAHUN 2009 - Riamah, - (Sistem Informasi, 2016)
Menopause is the permanent cessation of menstruation in a woman who generally occurs at age 50-51 years. Causes that trigger menopause is a disease such as tuberculosis of the ovary or ovarian cancer, lifestyle is wrong, the shift in eating patterns in some women, lazy to exercise, excessive exercise. This study is a correlational design approach croos sectional study aimed to examine the relationship between knowledge with maternal attitude toward menopause. The study population was 50 mothers aged 40-45 years, using total sampling method. Measuring instrument used was a questionnaire. From the results of the data collection characteristics of the respondents found the majority of respondents was 40 years old (46%), education level of the majority of high school educated are (46%), work as respondents (66%) did not work, whereas for information as much (66%) of respondents had get information and most received resources from books / magazines as many (28%). The analysis is Univariate and Bivariate. In this study as many (66%) of respondents have a high knowledge level (median = 8) and as many (58%) of mothers have a positive attitude (median = 45). The results of this study indicate that there is no relationship between the level of knowledge of the mothers attitude toward menopause where Ï = 0:41> Î± = 0.05. This means that women who have high knowledge about menopause does not affect the mothers attitude to be positive as well as negative because of the difference between high and low knowledge that has positive and negative attitudes not too siqnifikan.